EFFECT OF ALCOHOLIC ANASTATICA HIEROCHUNTICA EXTRACTON SOME BIOCHEMICAL AND HISTOLOGICAL PARAMETERS INALLOXAN INDUCED DIABETIC RATS - Shaban, Feryal; Al-Azzawie, Hasan; Mohammed, Ali (Iraqi Journal of Science, 2024)
The methanolic extract of Anastatica hierochuntica was investigated for itsantidiabetic effect in male Albino rats. Blood glucose levels, lipids profile weresignificantly reduced in all treated group of alloxan diabetic rats in comparison totheir pre-treatment values, in addition to, intake of orally dose of 100 mg/kg b.w ofmethanolic extract daily for four consecutive weeks to diabetic rats significantlydecreased the activity levels of all those biomarker liver damage enzymes (S.GOT,S. GPT and S.ALP), and restored it to normal values. Levels of SOD activity weresignificantly decreased in diabetic rats compared with the healthy group, but theselevels increased significantly to a value similar to the healthy rat when treated witha daily single dose of Anastatica hierochuntica extract ( 100mg/kg b.w) for fourweeks. The same pattern was seen with another antioxidant enzyme GPx, its levelssignificantly decreased in diabetic and increased when the animals fed on the extractdaily for four weeks. Histopathological observations in both pancreas and liver rat'stissues revealed that methanolic Anastatica hierochuntica extract was non-toxic andregenerated the toxic effects of alloxan. In conclusion the decreased blood glucoseaccompanied with decreased lipid profile and changes in the activities of theantioxidant enzymes SOD and GPx, in addition to biomarker liver damage enzymesshowed the antidiabetic, hypolipidmic and a potent antioxidant agent.